2008
DOI: 10.1007/s00423-008-0439-7
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of neutrophils with silver-coated vascular polyester grafts

Abstract: The results may indicate that silver-coated vascular polyester grafts activate neutrophils chronically which may favor tissue destruction and impaired antimicrobial effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…The well-known antimicrobial activity of nanosilver account for the application in medicine such as coatings of catheters or implant material [26][27][28], however, there are case reports of adverse reaction after the use of topical wound dressings which release silver nanoparticles [29]. This study demonstrates that silver nanoparticles exert cytotoxic effects on hMSCs at high concentrations but also induce cell activation (as analyzed by the release of IL-8) at high but nontoxic silver concentrations.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The well-known antimicrobial activity of nanosilver account for the application in medicine such as coatings of catheters or implant material [26][27][28], however, there are case reports of adverse reaction after the use of topical wound dressings which release silver nanoparticles [29]. This study demonstrates that silver nanoparticles exert cytotoxic effects on hMSCs at high concentrations but also induce cell activation (as analyzed by the release of IL-8) at high but nontoxic silver concentrations.…”
Section: Discussionmentioning
confidence: 70%
“…Additionally, it was reported that the exposure of carcinoma cells (TR146) with toxic nickel concentrations led to a dramatic increase in arachidonic acid-derived mediators, thus, the involvement of lipid mediators may be involved in the induction of IL-8 by divalent metal ions. Recently, it was also shown that neutrophils were activated at silver-coated vascular polyester grafts in vitro and responded with the release of lipid mediators (leukotriene B4) and IL-8 [27]. The release of chemokines such as IL-8 and other proinflammatory cytokines from osteoblasts or monocytes/macrophages has been described for various microscale particles.…”
Section: Discussionmentioning
confidence: 98%
“…For example, while silver sulfadiazine effectively prevents infection, it can inhibit proliferation of keratinocytes and fibroblasts [72]. Silver nitrate treatments have been shown to promote apoptosis of these cell types, and studies have suggested that silver promotes the chronic activation of neutrophils [73,74].…”
Section: Discussionmentioning
confidence: 99%
“…In their report, Tautenhahn et al demonstrated that silver-coated vascular polyester grafts highly activate human neutrophils when compared with regular polyester grafts, causing the neutrophil to release high levels of elastase (a very destructive enzyme) in the absence of a bacterial trigger. 10 On the contrary, Jeanmonod et al 11 provide evidence in vivo that silver acetate (used in the Maquet graft), does not induce a leukocyte-mediated tissue inflammatory response, but in fact stimulates ingrowth of microvessels, promoting implant incorporation.…”
Section: Discussionmentioning
confidence: 99%